Pharmacognostical and preliminary phytochemical investigation of Equisetum debile Roxb. - Sharma, Preksha; Mohanty, J. P.; Ghosh, Pallab; Sharma, Chandrika; Subba, Bhupen (Journal of Drug Delivery and Therapeutics, 2019)
Herbal medicines are increasingly gaining popularity as they possess minimal or no side effects therefore, authentication of the crude drugs are necessary to ensure that the herbal drugs so obtained are safe and of optimal quality. In the present study, various pharmacognostical parameters such as organoleptic evaluation, macroscopic evaluation, microscopic evaluation, physico chemical evaluation (moisture content, loss on drying, ash values, extractive values), and phytochemical evaluation were conducted for the plant E. debile Roxb. (Equisetaceae). Pharmacognostic evaluation helps to identify the commercial varieties, substitutes, adulterants and any other quality control parameter of the drugs. It is a simple and reliable tool, by which complete information of the crude drugs can be obtained (WHO 1998). Pharmacognostical evaluation helps to establish the authenticity of the drugs, it also helps to differentiate the drugs from other species and it also helps to detect any form of adulteration. Keywords: Equisetum debile Roxb., pharmacognostical, organoleptic evaluation, phytochemical analysis.